2020
DOI: 10.1080/02688697.2020.1787948
|View full text |Cite
|
Sign up to set email alerts
|

Extended lumbar drainage in idiopathic normal pressure hydrocephalus: a systematic review and meta-analysis of diagnostic test accuracy

Abstract: Background: When appropriately selected, a high proportion of patients with suspected idiopathic normal pressure hydrocephalus (iNPH) will respond to cerebrospinal fluid diversion with a shunt. Extended lumbar drainage (ELD) is regarded as the most accurate test for this condition, however, varying estimates of its accuracy are found in the current literature. Here, we review the literature in order to provide summary estimates of sensitivity, specificity, positive-and negative predictive value for this test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…There is a paucity of data regarding the sensitivity and specificity of ELD and HVLP in predicting shunt responsiveness, because most studies do not shunt patients who do not improve clinically after temporary CSF diversion. A recent meta-analysis of ELD as a diagnostic test for HS found varying results [33]. The investigators found only four small studies in which patients (n=84) having ELD underwent shunt surgery regardless of the outcome.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…There is a paucity of data regarding the sensitivity and specificity of ELD and HVLP in predicting shunt responsiveness, because most studies do not shunt patients who do not improve clinically after temporary CSF diversion. A recent meta-analysis of ELD as a diagnostic test for HS found varying results [33]. The investigators found only four small studies in which patients (n=84) having ELD underwent shunt surgery regardless of the outcome.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…The advance of brain imaging could help detect secondary structural lesions, which exhibit a clinically similar presentation [ 12 ]. Even extended lumbar drainage use provides a better prognostic value for testing the diagnosis of iNPH, preoperative evaluation considering clinical symptoms, radiological findings, CSF biomarkers of iNPH, and neurophysiological signatures may ensure a higher effectiveness of shunt surgery [ 49 50 ].…”
Section: Ultimodality Treatment For Idiopathic Normal Pressure Hydroc...mentioning
confidence: 99%
“…Meta-analyses have subsequently confirmed that the CSF tap test has a high positive predictive value and that external lumbar drainage also has a high specificity (~85% with wide confidence intervals) but there is no perfect predictive test for shunt responsiveness 24 25…”
Section: Provocative Testingmentioning
confidence: 99%